Sacrificers' Preferences on Selection and Procurement of Sacrificial Animals for Eid al-Adha Celebration - Ibrahim, Alek; Budisatria, I Gede Suparta; Artama, Wayan Tunas; Widayanti, Rini; Atmoko, Bayu Andri (ANIMAL PRODUCTION, 2022)
Eid al-Adha is one of the biggest religious celebrations in Indonesia. This study was conducted to determine the profile and activities of sacrificers (shohibul qurban) in selecting and procuring sacrificial animals for the Eid al-Adha celebration. This study was conducted by in-depth interviews with a total of 54 sacrificers in Sleman Regency, Yogyakarta, during the Eid al-Adha celebration in 2019. The data were analyzed using descriptive analysis (number and percentage). This study indicated that most sacrificers were classified as productive age (45.35 years), high school graduates (46.30%), and self-employed workers (50.00%) with an income of IDR 3,357,896 per month. The sacrificial animals were cattle, sheep, and goats with an average body weight of 253.75 kg, 27.80 kg, and 32.80 kg, and the prices of IDR 20,939,962; IDR 2,906,250; and IDR 2,420,000, respectively. The sacrificial animals were mainly purchased from the livestock seller or intermediary seller (38.89%). There were livestock-price differences in the different marketplaces (44.44%) and between Eid al-Adha and the daily period (61.11%). This study concluded that the cattle preferred animal types for group sacrifices, and the sheep had preferred animal types for individual sacrifice. Cattle are usually sacrificed with a joint purchase between sacrificers. Each reason for selecting and procuring the sacrificial animal types was influenced by different motivations, such as financial, animal handling, and local wisdom factors.